Therapeutical approach to plasma homocysteine and cardiovascular risk reduction - Marcello Ciaccio; Giulia Bivona; Chiara Bellia (Dove Medical Press, 2008)
Marcello Ciaccio, Giulia Bivona, Chiara BelliaDepartment of Medical Biotechnologies and Forensic Medicine, Faculty of Medicine, University of Palermo, ItalyAbstract: Homocysteine is a sulfur-containing aminoacid produced during metabolism of methionine. Since 1969 the relationship between altered homocysteine metabolism and both coronary and peripheral atherotrombosis is known; in recent years experimental evidences have shown that elevated plasma levels of homocysteine are associated with an increased risk of atherosclerosis and cardiovascular ischemic events. Several mechanisms by which elevated homocysteine impairs vascular function have been proposed, including impairment of endothelial function, production of reactive oxygen species (ROS) and consequent oxidation of low-density lipids. Endothelial function is altered in subjects with hyperhomocysteinemia, and endothelial dysfunction is correlated with plasma levels of homocysteine. Folic acid and B vitamins, required for remethylation of homocysteine to methionine, are the most important dietary determinants of homocysteine and daily supplementation typically lowers plasma homocysteine levels; it is still unclear whether the decreased plasma levels of homocysteine through diet or drugs may be paralleled by a reduction in cardiovascular risk.Keywords: homocysteine, MTHFR, cardiovascular disease, folate, B vitamin